2009
DOI: 10.1161/circulationaha.108.843516
|View full text |Cite|
|
Sign up to set email alerts
|

Proteomic Analysis in Aortic Media of Patients With Marfan Syndrome Reveals Increased Activity of Calpain 2 in Aortic Aneurysms

Abstract: Background-Marfan syndrome (MFS) is a heritable disorder of connective tissue, affecting principally skeletal, ocular, and cardiovascular systems. The most life-threatening manifestations are aortic aneurysm and dissection. We investigated changes in the proteome of aortic media in patients with and without MFS to gain insight into molecular mechanisms leading to aortic dilatation. Methods and Results-Aortic samples were collected from 46 patients. Twenty-two patients suffered from MFS, 9 patients had bicuspid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 42 publications
3
50
0
Order By: Relevance
“…61 Changes in the VSMC phenotype are also reported in other aortic aneurysms 21,22 in a murine model of MFS. 62 Our results are largely coincident with those obtained after the proteomic analysis of the tunica media of human Marfan aneurysms, 63 which report strong upregulation of calponin1, filamin A, and vinculin among other contractile proteins. However, this coincidence does not extend to transgelin (SM22α), which in the study by Pilop et al 63 was downregulated, but that in our Marfan aortic aneurysms showed variability and even reduced at transcriptional level in cultured Marfan cells.…”
Section: Pathophysiological Significance Of Phenotypic Changes Of Vsmsupporting
confidence: 87%
See 1 more Smart Citation
“…61 Changes in the VSMC phenotype are also reported in other aortic aneurysms 21,22 in a murine model of MFS. 62 Our results are largely coincident with those obtained after the proteomic analysis of the tunica media of human Marfan aneurysms, 63 which report strong upregulation of calponin1, filamin A, and vinculin among other contractile proteins. However, this coincidence does not extend to transgelin (SM22α), which in the study by Pilop et al 63 was downregulated, but that in our Marfan aortic aneurysms showed variability and even reduced at transcriptional level in cultured Marfan cells.…”
Section: Pathophysiological Significance Of Phenotypic Changes Of Vsmsupporting
confidence: 87%
“…62 Our results are largely coincident with those obtained after the proteomic analysis of the tunica media of human Marfan aneurysms, 63 which report strong upregulation of calponin1, filamin A, and vinculin among other contractile proteins. However, this coincidence does not extend to transgelin (SM22α), which in the study by Pilop et al 63 was downregulated, but that in our Marfan aortic aneurysms showed variability and even reduced at transcriptional level in cultured Marfan cells. Moreover, VSMC explanted from heterozygous TGFβR2 mutations decreased global expression of contractile proteins and failed to increase their expression after exposure to the cytokine, which was attributed to the disruption of TGF-β signaling.…”
Section: Pathophysiological Significance Of Phenotypic Changes Of Vsmsupporting
confidence: 87%
“…Marfan syndrome is caused by mutations in fibrillin-1 gene, and its most serious manifestation is aortic aneurysm and dissection of the ascending aorta (45). Importantly, MFAP4 protein is up-regulated in ascending aortic samples from patients suffering from Marfan syndrome (46), suggesting that MFAP4 might play an important role in Marfan syndrome pathology and aneurysm formation.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that calpains were involved in the development of Ang IIinduced vascular remodelling (4). Additionally, the activation of calpains has been identified in several types of cardiovascular diseases, including aortic aneurysm and diabetic cardiomyopathy (17,18). Furthermore, inhibition of calpains by treatment with a pharmacological inhibitor or overexpression of calpastatin may protect the heart from ischemiareperfusion injury (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%